Hitting the right note for child and adolescent mental and emotional wellbeing: a formative qualitative evaluation of Sistema Scotland's "Big Noise" orchestral programme. Issue 1 (21st March 2016) - Harkins, Christopher; Garnham, Lisa; Campbell, Aileen; Tannahill, Carol
Abstract : Purpose: – Previous research emphasises the need for preventative interventions to reduce mental health problems among disadvantaged children and adolescents. There is however little consensus concerning the delivery and impacts of such interventions particularly non-clinical, arts-based models delivered within community settings. The purpose of this paper is to begin to address this deficit through a qualitative assessment of the short- to medium-term impacts to participants' mental and emotional wellbeing within Sistema Scotland's Big Noise orchestral programme. Design/methodology/approach: – Semi-structured interviews, observation, participant drawing exercise, participatory filmmaking, focus group and analysis of programme engagement were undertaken to examine the mental and emotional wellbeing impacts of the programme which are observable at this early stage of programme delivery and participants' lives. Findings: – The qualitative findings indicate that participation in the Big Noise programme enhances participant mental and emotional wellbeing in three ways; first, the happiness and enjoyment of taking part in the programme and orchestra, particularly from music making; second, the security, belonging and relationships fostered through participation; the quality of musician/participant relationship is important here as is programme design which enables support, routine and structure; and third, increased pride, confidence and self-esteem, as a result of acquiring difficult musical skills, receiving regular praise and having frequent opportunities to demonstrate these acquired skills through regular orchestral performances. Originality/value: – There is little evidence or understanding of community-based, preventative, arts interventions like Big Noise: their delivery, their life-course impacts and their potential contribution to mental health and to addressing social and health inequalities. The causal pathways in the field are under-theorised. These early findings are important as they serve as an important basis from which to consider the programme's wider and longer term impacts, which will be assessed through an on-going longitudinal, mixed method summative evaluation.